Implementation of Web-based Supply Chain Management for Drug Stock Control - Cristifani, Cristifani; Riki Andri Yusda; Rohminatin, Rohminatin (The Indonesian Journal of Computer Science, 2023)
The problems that are often faced at aesthetic clinics are managing drug data and checking the availability of the drug stock itself, which is still less effective and product sales transactions differ between transaction notes received by customers and goods coming out of the warehouse. Because in one day if several patients buy drugs in sufficient quantities, thus the stock in the warehouse will also be running low. Often there is a shortage of medicine stock because they don't check and count every medicine in the warehouse.